Effect of Hysteroscopic Surgery Before Frozen Embryo Transfer on Patients with Previous Implantation Failure - Abdullah Tok; Cihan Çetin; Caglar Cetin; Dilek Kaya Kaplanoğlu; M.turan Çetin; Ayşe Filiz Gokmen Karasu; İlay Öztürk (Düzce Tıp Fakültesi Dergisi, 2022)
Aim: The aim of this study was to evaluate the benefit of hysteroscopy (HS) before single frozen-thawed embryo transfer (sFET) on patients with previous implantation failure. Material and Methods: A total of 1352 infertile women with a previous implantation failure who underwent their first sFET treatment between January 2015 and December 2017 were included in this study. The patients were classified into two main groups in which HS was omitted (Group 1), and who underwent HS (Group 2). Furthermore, Group 2 was classified into two subgroups as patients without any intrauterine pathology (Group 2a), and those with intrauterine pathology (Group 2b). sFET was performed on all patients within 50 days of hysteroscopy. The major outcome measure was the clinical pregnancy rate. Results: The mean number of mature oocytes and fertilization rates were similar between groups. The clinical pregnancy rate was found to be 33.3% (n=70) in Group 1. Comparatively this rate was statistically significantly higher in patients in Group 2. The clinical pregnancy rate was 44.2% (n=378) in Group 2a, and 44.4% (n=127) in Group 2b (p=0.014). There was a significant difference between Group 1 and Group 2a (OR: 1.58, 95% CI: 1.15-2.17, p=0.004), and also Group 2b (OR: 1.59, 95% CI: 1.10-2.31, p=0.013). However, no significant difference was observed between Group 2a and Group 2b (p=0.896). Conclusion: Our findings demonstrate that HS surgery increases the probability of pregnancy rate at least by 1.58 times in patients having previous implantation failure when the hysteroscopic procedure is followed by sFET.